Democracy and Islam in Malek Bennabi's Thought - Yahia H. Zoubir (International Institute of Islamic Thought, 1998)
The growth of political Islam in the 1970s and the possibility of Islamist parties coming to power in various countries led many scholars and political analysts to question the compatibility of Islam and democracy. Most studies have concentrated on popular Muslim thinkers who were considered Islamic activists such as Sayyid Qutb or Abu ‘Ala Al- Maududi, but no attention has been paid to the thought of the remarkable Algerian Islamic thinker, Malek Bennabi (1905-1973). A French-educated electrical engineer, strongly influenced by the ideas of Rashid Rida and Mohammed Abdu, Bennabi’s most important concern throughout his life was the adaptation of Islamic values to modernity. Very familiar with western civilization-as well as many others-he felt that the Muslim world failed to rise above its inertia not only because it is incapable of absorbing modem technology, but also because its elite borrowed failing ideologies, such as Marxism, without attempting to recapture the best values that were produced by Islamic civilization. In other words, the Muslim world failed to reproduce the experience of such successful nations as Japan. In his view, Japan achieved modernity because “the ‘deadly ideas’ [i.e., materialism] of the west did not make it deviate from its path: It [Japan] remained faithful to its culture, its traditions, and its past.”’ More importantly, throughout his work Bennabi puts most of the blame for the Muslim world‘s predicament, not on western colonialism, but on the Islamic world itself, a notion that m s against the prevailing opinion in the Arab-lslamic world that argues that western powers are mostly responsible for the backwardness of the Muslim world. After his return to Algeria in 1963, following his long exile in Egypt, Malek Bennabi joined the first Islamist organization in Algeria, Al-Qiym al-slamyya (Islamic Values), founded the same year. The association was opposed to the “Marxist” policies of President Ahmed ...